2005
DOI: 10.1002/anie.200501681
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of [all]‐S,S‐Dioxide Oligothiophenes Using HOF⋅CH3CN

Abstract: Nonaromatic stable polyenes are obtained by dioxygenation of oligothiophenes using HOF⋅CH3CN prepared in situ by passing F2 through aqueous acetonitrile (see scheme). These fully S,S‐dioxygenated derivatives have a considerably smaller HOMO–LUMO gap than the parent compounds; furthermore, in the solid state they tend to form favorable π–π stacking interactions, unlike most non‐oxidized oligothiophenes which adopt the “herringbone” motif.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 38 publications
2
60
1
Order By: Relevance
“…249 Amir and Rozen recently developed a new elegant method for the preparation of all-S,S-dioxide oligothiophenes 2.153 by treatment of alkyl-capped oligothiophenes 2.152 with oxygen transfer agent HOF · CH 3 CN, which possesses a truly electrophilic oxygen center. 250 The synthetic route provided high yielding and rapid S,S-dioxide transformations (1-40 min at 0 to -10°C, Scheme 2.27) without formation of regioisomers as previously reported by the Barbarella group. Compared to starting materials and partially oxygenated S,Sdioxides, which showed a single broad absorption band, the corresponding all-S,S-dioxides displayed structured bands due to the rigidification of the π-conjugated backbone.…”
Section: Oligothiophene Ss-dioxidesmentioning
confidence: 72%
“…249 Amir and Rozen recently developed a new elegant method for the preparation of all-S,S-dioxide oligothiophenes 2.153 by treatment of alkyl-capped oligothiophenes 2.152 with oxygen transfer agent HOF · CH 3 CN, which possesses a truly electrophilic oxygen center. 250 The synthetic route provided high yielding and rapid S,S-dioxide transformations (1-40 min at 0 to -10°C, Scheme 2.27) without formation of regioisomers as previously reported by the Barbarella group. Compared to starting materials and partially oxygenated S,Sdioxides, which showed a single broad absorption band, the corresponding all-S,S-dioxides displayed structured bands due to the rigidification of the π-conjugated backbone.…”
Section: Oligothiophene Ss-dioxidesmentioning
confidence: 72%
“…The chemical synthesis of the studied compounds has been previously published [2]. The data presented in this paper for the oligoenes are those available in the literature [3].…”
Section: Experimental and Theoretical Detailsmentioning
confidence: 99%
“…[4] reported a class of oligothiophene-S,S-dioxides and their research revealed that the insertion of nonaromatic thiophene-S,S-dioxide (TO) units within the skeleton of conjugated polymers to form donor-acceptor co-polymers/ oligomers is very promising for use as field-effect transistors and other optoelectronic devices. Now, research on TOs is growing rapidly [5] and TO-containing compounds [6][7][8][9][10][11][12] can emit light under UV excitation with frequencies covering the entire visible range (from the UV to the NIR) and display high photoluminescence efficiencies (some even up to 70%). In the last few years, extensive research has been also devoted to incorporation of benzothiophene-S,S-dioxide (BTO) [13][14][15] and dibenzothiophene-S,S-dioxide (DBTO) [16][17][18][19][20][21][22][23][24][25][26][27][28] units into various conjugated polymers.…”
Section: Introductionmentioning
confidence: 99%